(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Essential hypertension is associated with altered pulmonary function. Antihypertensive medication and lung function are also associated. Losartan (angiotensin II receptor blocker) and atenolol (beta blocker) are commonly used antihypertensive drugs. Objective: To evaluate the effects of antihypertensive drugs on lung function status in patients with essential hypertension. Methods: This prospective observational study was carried out in the Department of Physiology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka, from July 2012 to June 2013 on 100 newly diagnosed essential hypertensive patients who had not received any antihypertensive medications. They were selected from the Out Patient Department (OPD) of Cardiology unit, BSMMU, Dhaka. The study sbujects of age between 30-55 were allocated in group B. Based on prescribed treatment, these study subjects were divided into two groups - B1 and B2. B1 included 50 patients who received losartan 50mg daily and B2 included 50 patients who received atenolol 50mg daily. Again basing on duration of treatment group B1 was divided into B1a (newly diagnosed hypertensive patients before treatment), B1b (after 3 months of medication with losartan) and B1c (after 6 months medication with losartan). Similarly group B2 was divided into B2a, B2b, and B2c. For assessing lung function status, FVC, FEV1 and PEFR were measured with acomputer based Spirometer. Age, sex and BMI matched 50 apparently healthy normotensive subjects were also studied as control (group A). Data were compared among subjects of different groups. For statistical analysis independent sample t test and paired sample t test were performed. Results: Mean systolic blood pressure and diastolic blood pressure were significantly higher and mean FVC, FEV1 and PEFR were significantly lower in newly diagnosed hypertensive patients in comparison with that of healthy normotensive subjects. Mean FVC and FEV1 were found significantly higher in the group taking losartan for 6 months when compared to newly diagnosed hypertensive patients but lower than those of controls. In addition, mean FVC and FEV1 were found significantly lower in the group taking atenolol for 6 months when compared to newly diagnosed hypertensive patients and those of controls. Conclusion: Reduced lung function occurs in newly diagnosed essential hypertensive patients which improves by treatment with losartan but decreases after treatment with atenolol. Journal of Armed Forces Medical College Bangladesh Vol.10(2) 2014